A new freeware tool for image processing and its application to high speed LA-ICP-MS imaging. Issue 7 (1st May 2019) - Managh, Amy J.; Reid, Peter
Abstract : New LA-ICP-MS imaging software has been developed and applied to perform fast, high spatial resolution imaging of zinc in retina tissue. Abstract : A new standalone, non-commercial software application has been developed to enable rapid generation of images from laser ablation-inductively coupled plasma-mass spectrometry data. The software locates peaks within raw data files and uses the peak locations to segment the data at appropriate intervals, enabling conversion of the data into a matrix of colour coded pixels. The app was developed in order to process baseline separated peaks produced by the latest generation of low-dispersion laser ablation systems, but it is equally applicable to rastered imaging using alternative laser ablation platforms. The peak recognition feature also has applicability to single cell and single particle ICP-MS applications. The app was demonstrated for the imaging of zinc in a stained section of rat retina tissue at lateral resolutions down to 1 μm. Less than two minutes was required for conversion of the raw data into a 60 000 pixel image.